Impact of small sided games on decision making and technique on U-12 football players: effect of closed area - Pérez Muñoz, Salvador; Recouvreur Encinas, David; Sánchez Muñoz, Antonio; Rodríguez Cayetano, Alberto (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of the research was to analyze how the practice of small sided games influences technique and decision-making in U-12 football players male, with modification of the space. There were 12 U-12 players participating. They carried out 20 training sessions based on small sided games of football on a playing field that is surrounded by walls generating an enclosed playing space. The sample showed normal values in the Saphiro-Wilk test. The main results show that there are significant differences in the pass and control variables, and there is a significant improvement in the execution and decision-making actions. Decision-making showed significant differences in all the indicators. Therefore, it improves the technique and decisions in specific game situations, through the use of small sided games, in this way it can be considered as a methodological resource to be used in these training phases.